Neurodevelopmental outcome of low-risk moderate to late preterm infants at 18 months - Mary Anne Ryan; Mary Anne Ryan; Deirdre M. Murray; Deirdre M. Murray; Eugene M. Dempsey; Eugene M. Dempsey; Eugene M. Dempsey; Sean R. Mathieson; Sean R. Mathieson; Vicki Livingstone; Vicki Livingstone; Geraldine B. Boylan; et al. (Frontiers Media S.A., 2023)
BackgroundOf the 15 million preterm births that occur worldwide each year, approximately 80% occur between 32 and 36 + 6 weeks gestational age (GA) and are defined as moderate to late preterm (MLP) infants. This percentage substantiates a need for a better understanding of the neurodevelopmental outcome of this groupAimTo describe neurodevelopmental outcome at 18 months in a cohort of healthy low-risk MLP infants admitted to the neonatal unit at birth and to compare the neurodevelopmental outcome to that of a healthy term-born infant group.Study design and methodThis single-centre observational study compared the neurodevelopmental outcome of healthy MLP infants to a group of healthy term control (TC) infants recruited during the same period using the Griffith's III assessment at 18 months.ResultsSeventy-five MLP infants and 92 TC infants were included. MLP infants scored significantly lower in the subscales: Eye-hand coordination (C), Personal, Social and Emotional Development (D), Gross Motor Development (E) and General Developmental (GD) (p < 0.001 for each) and Foundations of Learning (A), (p = 0.004) in comparison to the TC infant group with Cohen's d effect sizes ranging from 0.460 to 0.665. There was no statistically significant difference in mean scores achieved in subscale B: Language and Communication between groups (p = 0.107).ConclusionMLP infants are at risk of suboptimal neurodevelopmental outcomes. Greater surveillance of the neurodevelopmental trajectory of this group of at-risk preterm infants is required.